Assessing the short‐term effects of capture, handling and tagging of sandgrouse. (18th November 2014) - Casas, Fabián; Benítez‐López, Ana; García, Jesús T.; Martín, Carlos A.; Viñuela, Javier; Mougeot, Francois; Marsden, Stuart
<x xml:space="preserve">Abstract</x> Capturing and marking free‐living birds permits the study of important aspects of their biology but may have undesirable effects. Bird welfare should be a primary concern, so it is necessary to evaluate and minimize any adverse effects of procedures used. We assess short‐term effects associated with the capture, handling and tagging with backpack‐mounted transmitters of Pin‐tailed Pterocles alchata and Black‐bellied Pterocles orientalis Sandgrouse, steppe birds of conservation concern. There was a significantly higher mortality (15%) during the first week after capture than during the following weeks (< 2.5%) in Pin‐tailed Sandgrouse, but no significant temporal mortality pattern in Black‐bellied Sandgrouse. In Pin‐tailed Sandgrouse, mortality rate during the first week increased with increasing relative transmitter and harness weight regardless of season, and with increasing handling time during the breeding season. There were no significant differences in mortality rate between study areas, type of tag, sex or age or an effect of restraint time. These results suggest the use of lighter transmitters (< 3% of the bird's weight) and a reduction of handling time (< 20 min), particularly during the breeding season, as essential improvements in procedure to reduce the mortality risk associated with the capture, handling and tagging of these vulnerable species.